Essential oil from five alpinia species of Sarawak - Nur Hidayah, Azeman (Universiti Malaysia Sarawak, UNIMAS, 2009)
Essential oils from five species of Alpinia were investigated for their chemical composition and biological activity against Artemia salina, Coptotermes sp and fungi species; Trametes Versicolor, Gloeophyllum Trabeum and Chaetomium. Essential oil was extracted by using hydrodistillation method and subsequently analyzed by using gas chromatography/flame ionization detector (GC/FID). The percentages of essential oil obtained from five Alpinia species ranged from 0.37% (v/w) to 2.56% (v/w). Generally, the highest value of 2.56% (v/w) was obtained from rhizome of A. latilabris, while the lowest yield obtained from stem of A. latilabris with the percentage of 0.37% (v/w). Leaves of A. amentaceae were rich in β-carene (87.33%) and ocimene (5.90%) while ethylpyrazine (50.67%) and nonane (35.10%) was the major compound in rhizome oil. The most abundant compound in A. aquatica (Campus) was β-bourbonene (16.83%) and hexanithiol (12.58%), from leaves oil and 2-dodecenal (38.26%) from rhizome oil. The major compound was found in the leaves of A. nieuenhuizii was β-pinene (36.35%) and 2-pentanol (22.02%) in rhizome oil. In the A. latilabris the major compound found in leaves oil was wine lactone (16.66%) and dimethyl pyrazine (16.43%), while in stem oil was ethylpyrazine (50.32%) and dimethyl pyrazine (26.22%) was found in rhizome oil. A. aquatica (Lawas) was found to be rich in 2-pentanol (58.99%) for leaves oil, furfuryl mercaptan (39.66%) for stem oil and 2-dodecenol (17.30%) for rhizome oil. The bioassay tests against A. salina for Alpinia sp. have not shown any biological activity. Termicidal test on Coptotermes sp showed that the leaves oil of A. aquatica (Lawas) gave significant value with the LC50 of 0.75%, while the rhizome oil of A. aquatica (Lawas) showed no significant value with the LC50 of 1.50%. The antifungal test on Alpinia sp. showed no biological activity.